Glottic configuration changes and outcomes of endoscopic arytenoid abduction lateropexy - Szakács László (EUROPEAN ARCHIVES OF OTO-RHINO-LARYNGOLOGY, 2019)
Endoscopic arytenoid abduction lateropexy (EAAL) is an effective glottis enlarging procedure for the treatment of bilateral vocal cord palsy (BVCP). The postoperative glottic configuration changes can be evaluated by modern, high-resolution, 3D image reconstructions. Functional results are described by spirometry as well as objective and subjective phoniatric tests.Unilateral EAAL was performed in ten malignant thyroid gland tumor patients (eight women, two men), who had BVCP after thyroid surgery. Slicer 3D® software was used for morphometric analysis. Pre- and postoperative peak inspiratory flow (PIF) and standard phoniatric parameters were compared.The glottic gap improved significantly (+ 60%). Significant improvement of PIF was found in all cases. Phoniatric tests revealed better quality of voice and patient satisfaction. Their voices changed from a severely impaired to a socially acceptable, almost normal, quality.The results support our clinical observations that the ideal position of the lateralization sutures is the one which provides a physiological abduction position of the arytenoid cartilage. Considering these good results, the surgical indications for minimally invasive endoscopic arytenoid lateropexy may be extended.